Having an Eating Disorder and Still Being Able to Flourish? Examination of Pathological Symptoms and Well-Being as Two Continua of Mental Health in a Clinical Sample - de Vos, Jan Alexander; Radstaak, Mirjam; Bohlmeijer, Ernst T.; Westerhof, Gerben J. (Frontiers in Psychology, 2018)
Introduction. Eating Disorders (EDs) are serious psychiatric disorders, impacting physical and psychosocial functioning, often with a chronic course and high mortality rates. The two continua model of mental health states that mental health is a complete state, that is not merely the absence of mental illness, but also the presence of mental health. This model was studied among ED patients by comparing the levels of well-being to the Dutch general population and by examining the of well-being and psychopathology. Method. A total of 468 female ED patients participated in this study during application and intake at a specialized ED treatment centre in the Netherlands. They filled out questionnaires about well-being (MHC-SF), general psychopathology (OQ-45), and ED psychopathology (EDE-Q). Categorical and mean well-being levels were calculated. Also, the correlates of these variables were examined with Pearson correlation and multiple hierarchical regression analysis. Results. ED patients showed lower levels of emotional, psychological and social well-being on average compared to the general population. About 26% of the ED patients experienced low levels of well-being (languishing). However, also 13% experienced high levels of well-being (flourishing), varying between 9% in Anorexia Nervosa to 25% in Binge Eating Disorder. ED psychopathology and general well-being showed a moderate negative correlation. For patients with Bulimia Nervosa and Binge Eating Disorder however no such correlation was found. Lower general psychopathology, not having a history of hospitalization for the ED, and adaptive personal functioning were correlated with well-being among ED patients. Conclusion This study shows initial support for the two continua model of mental health among ED patients. Psychopathology and well-being should be considered as related, but distinct dimensions of mental health in ED patients. Further research should focus on the possible reciprocal relationships between psychopathology and well-being during recovery. It is recommended to monitor well-being during treatment and to implement interventions for well-being to realize complete recovery for those patients with inadequate levels of well-being.